2019
DOI: 10.1371/journal.pone.0218025
|View full text |Cite
|
Sign up to set email alerts
|

The child survival impact of the Ghana Essential Health Interventions Program: A health systems strengthening plausibility trial in Northern Ghana

Abstract: Background The Ghana Health Service in collaboration with partner institutions implemented a five-year primary health systems strengthening program known as the Ghana Essential Health Intervention Program (GEHIP). GEHIP was a plausibility trial implemented in an impoverished region of northern Ghana around the World Health Organizations (WHO) six pillars combined with community engagement, leadership development and grassroots political support, the program organized a program of training and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Comparison area CHPS coverage also improved, but at a much lower rate that achieved an end of project population coverage rate of half that of the treatment area. As a mechanism for improving health care equity, access, and effectiveness, GEHIP was shown to have had an impact on neonatal mortality 29 . And assessment of referral volume can maternal mortality ratios showed that emergency referral and facility based care strategies of the program saved maternal lives 30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparison area CHPS coverage also improved, but at a much lower rate that achieved an end of project population coverage rate of half that of the treatment area. As a mechanism for improving health care equity, access, and effectiveness, GEHIP was shown to have had an impact on neonatal mortality 29 . And assessment of referral volume can maternal mortality ratios showed that emergency referral and facility based care strategies of the program saved maternal lives 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Conducted in the Upper East Region over the 2010 to 2016 period, the GEHIP initiative greatly improved the provision of community-based primary health care through CHPS. The mortality impact of GEHIP on neonates was pronounced among neonates 29 . Mortality also declined significantly among children aged 1 to 59 months, but this trend was realized in both treatment and comparison areas owing to the successful improvement in IMCI care in all UER districts 31 .…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Recommendations emerging from this investigation focusing on leadership development strategies were assembled into interventions of a four district five-year experiment known as the Ghana Essential Health Interventions Programme (GEHIP) [33]. GEHIP tested means of improving the management of CHPS start-up activities and demonstrated ways to accelerate coverage, improve emergency referral services, and reduce mortality [34].…”
Section: Introductionmentioning
confidence: 99%